Identification of Paracetamol and Caffeine in Jamu Powders Simultaneously Using TLC-Densitometry - Wahyuningsih, Etik; Isnaeni, Isnaeni; Asri Darmawati; Annisa Kartika Sari (Universitas Airlangga, 2023)
Paracetamol and caffeine were chemical compounds suspected to be illegally added to traditional herbs claimed as rheumatics drugs. Identification of paracetamol and caffeine was conducted on five samples of jamu powder obtained from the Depot Jamu in Surabaya. This study aimed to simultaneously identify paracetamol and caffeine commonly found in traditional medicine, one of which was jamu powder, using thin-layer chromatography densitometry (TLC-Densitometry). Evaluation of the presence of paracetamol and caffeine in the product of jamu was performed by thin-layer chromatography with silica gel GF254 and chloroform-ethyl acetate (1:1) as the stationary and mobile phases, respectively. The spots on the TLC plate were detected using a UV light at 254 nm, and the areas were measured by a Camag TLC scanner. The TLC profile demonstrated good separation of paracetamol, caffeine, and other substances contained in the products. The retardation factors (Rf) of paracetamol and caffeine were 0,42 and 0,26, with detection limits of 0,0125 µg/spot and 0,05 µg/spot, respectively. The simultaneous identification of caffeine and paracetamol using thin-layer chromatography densitometry revealed that none of the five samples were detected to contain paracetamol and caffeine. Keywords: Simultaneously, Identification, Paracetamol, Caffeine, Jamu Powder, TLC- Densitometry